Geospatial Technologies for Hydric Erosion Management in the Llaucano River, Cajamarca 2024 - Gastolomendo Malimba, Edilberto; Huaman Bazan, Mariela Imasumac; Chilon De La Cruz, Vilma; Licapa Redolfo, Gladys Sandi (LACCEI, 2025)
This study aimed to evaluate the susceptibility to water erosion in the Llaucano River basin, located in Cajamarca, Peru, through the integration of geospatial technologies, multicriteria analysis, and territorial intelligence within a GIS environment. Due to increasing pressure on the soil from agricultural, urban, and mining activities in the area, official data from the Regional Government of Cajamarca and a Digital Elevation Model were used to generate the R, K, LS, C, and P factors. The results revealed an annual soil loss ranging from 1.01 to 5 t/ha/year, with a heterogeneous spatial distribution: 50.28% of the basin showed low susceptibility, 29.92% moderate, and 20.56% high to very high. The most critical areas coincided with steep slopes, shallow soils, and a lack of conservation practices. The analysis also identified forest fires as an aggravating factor, as they reduce vegetation cover. It is concluded that the implementation of integrated strategies for soil conservation, reforestation, and fire control is essential to mitigate soil loss and ensure the sustainability of the territory.